Heterogeneous effects of exogenous IL-2 on HIV-specific cell-mediated immunity (CMI). - Bell, S J (1992)
A characteristic feature associated with HIV-1 infection of the human host is a chronic decline in circulating CD4+ T helper/inducer cell numbers. Impaired cell-mediated immune functions usually occur in parallel with the decline in CD4+ T cells. Activated CD4+ T helper cells are a major source of endogenous IL-2 which is required for the immunoregulation of both antigen-specific B cells and CD8+ T cells. HIV-specific T cell proliferative responses are said to be weak and inconsistent, even during the asymptomatic phase of disease. We thus wished to determine how exogenous IL-2 affected HIV-specific T cell proliferation at different stages of the disease. Our cohort of 81 included both asymptomatic and symptomatic HIV-infected patients as well as uninfected normal donors. Proliferative responses of peripheral blood mononuclear cells (PBMC) that were elicited during culture with an immunodominant gp41-derived synthetic peptide, gp41[8], and which were known to be CD8+ cell-associated in asymptomatics only, were used to analyse the effects of exogenous IL-2. IL-2 had three main effects on HIV-specific proliferation, namely (i) an additive effect, (ii) a synergistic effect, and (iii) an induced effect. More specifically, low dose exogenous IL-2 frequently augmented lymphoproliferation in both asymptomatic and symptomatic gp41[8] responders. In most symptomatics, however, who were predominantly gp41[8] non-responders, exogenous IL-2 induced lymphoproliferation. Flow cytometric analyses using dual immunofluorescence were used to analyse the T cell subset distribution of proliferating PBMC cultures. During culture with gp41[8], both CD4+ and CD8+ T cell numbers increased. However, after the addition of exogenous IL-2 to gp41[8]-containing cultures, CD8+ cell-associated lymphoproliferative responses were preferentially augmented. These results suggest that in symptomatics there is an inadequate supply of endogenous IL-2 to help maintain the strong and effective CD8+ cell-associated anti-viral immunity, and an exogenous supply of IL-2 may be required.